1229. Evaluation of Colorectal and Hip/Knee Arthroplasty Surgical Site Infections at Ocean University Medical Center. (15th December 2022) - Ismail, Omar; Nissim, Yosef; Kerr, Nancy; Lake, Thomas; Dwivedi, Sukrut
Abstract: Background: A surgical site infection (SSI) is defined as an infection that occurs up to 30 days after surgery without an implant (or within one year if an implant is placed). The infection also must appear to be related to surgery. In 2021, there were 19 SSIs reported at Ocean University Medical Center (OUMC). These SSIs were associated with colorectal and hip/knee arthroplasty cases. The primary objective of this study is to evaluate appropriate preoperative antibiotic administration based on the type of surgical procedure. Some secondary objectives include the number of preoperative antibiotics administered and the appropriate timing of preoperative antibiotic administration. Methods: A retrospective observational evaluation was conducted on patients identified to have a SSIs from January 1, 2021, to December 31, 2021. Appropriate preoperative antibiotics were defined as the administration of guideline-recommended antibiotics for the given procedure. Appropriate timing of antibiotics was defined as antibiotics administered within guideline-recommended time frames prior to procedure start time. Descriptive statistics were used to analyze the results. Results: Of the 19 infections, ten were associated with colorectal procedures, and nine were associated with hip/knee arthroplasty procedures. Patients received preoperative antibiotics in 89% of the surgeries (17 of 19). We found that 71% (12 of 17) of patients received appropriate antibiotics determined by the surgical procedure. Of the five inappropriate antibiotic selection instances, two lacked appropriate bacterial coverage, while the other three covered the suspected pathogens but were not guideline-recommended agents. The timing of preoperative antibiotics was found to be appropriate in 76% of all surgeries. When assessing the overall compliance with antibiotic selection and timing, 58% (11 of 19) of cases followed all guideline recommendations. Conclusion: This study has identified areas of improvement regarding the antimicrobial selection and timing, documentation process of administration, and the use of order sets to combat inappropriate prescribing of surgical antimicrobial prophylaxis. Educational materials and in-services have been provided at OUMC. Disclosures: All Authors : No reported disclosures.